TANGGUNG JAWAB DEBITUR TERHADAP BENDA JAMINAN FIDUSIA YANG MUSNAH DALAM PERJANJIAN KREDIT BANK - Dwi Julia Ramaswari, Dewa Ayu; Wyasa Putra, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014)
This paper is about the responsibility of the debtor to object fiduciary assurancethat destroyed the bank credit agreement. The problems that occur that are blurring thenorm in Article 25 of Law number 42 of 1999 on Fiduciary objects in the context of theguarantees given by the debtor to the bank saddled fiduciary assurance apparentlydestroyed. This paper aims to grasp and understand the responsibility of the debtor toobject fiduciary assurance that destroyed the bank credit agreement. This writing, usingthe method of normative legal research with the type of analytical approach legislation(State approach). This paper presented a study that the responsibility of the debtor tothe destruction of the collateral in the loan agreement is a consequence of the eventsthat occurred. The responsibility of the debtor to guarantee the moving objects are stillmissing Credit to the lender to repay the loan. Regarding the movement or transfer ofproperty rights concerned must still refer to the legal system warranty, whichguarantees that the receiving party or creditor does not become the owner of a fullyjustified on the object, the legal consequences if a problem arises due to the fault of theemployer fiduciary with respect to the use or transfer of objects fiduciary security, thenthe fiduciary exempt from responsibility. In other words, the giver full fiduciaryresponsibility.
Keywords: Responsibility, Debtor, Bank Credit Agreement, Destroyed